2005
DOI: 10.1093/jpepsy/jsj038
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Appraisal and Coping with Pain: Relation to Maternal Ratings of Worry and Restriction in Family Activities

Abstract: Health care providers should assess patients' pain beliefs, correct misperceptions about pain seriousness, and help increase patients' perceived efficacy in coping with pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 29 publications
1
30
1
5
Order By: Relevance
“…39 Other psychosocial factors may play a major role in the co-occurrence of FGID in pediatric patients with CD. Mother IBS status, 40 stress, 41 somatization, 42,43 attention to pain, 44,45 social threat, 45 parental reluctance to accept the diagnosis, 46 and family adaptation 47 are all factors that have been found to promote FGID development and were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…39 Other psychosocial factors may play a major role in the co-occurrence of FGID in pediatric patients with CD. Mother IBS status, 40 stress, 41 somatization, 42,43 attention to pain, 44,45 social threat, 45 parental reluctance to accept the diagnosis, 46 and family adaptation 47 are all factors that have been found to promote FGID development and were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to pain (i.e., solicitous or protective responses) has been the most studied parental behavior. This concept is theoretically derived from social learning theory and is demonstrated by more solicitous responses from parents (i.e., frequent attending to pain symptoms, granting permission to avoid regular activities) toward their children’s pain behaviors being related to increased disability in children with recurrent and chronic pain (e.g., Claar, Simons, & Logan, 2008; Lipani & Walker, 2006; Walker & Zeman, 1992). …”
Section: Parent Level Influencesmentioning
confidence: 99%
“…Pain interferes with normal school attendance and performance, peer relationships and participation in family and personal activities. [25][26][27][28] One out of 10 children with functional abdominal pain attends school regularly while more than 28% of patients have absenteeism greater than one day in 10. [27] Data from adults have shown that patients who suffer from FGIDs may also endure sleep diffi culties, headaches, dizziness and fatigue.…”
Section: Morbiditymentioning
confidence: 99%